Kepastian Hukum dalam pasal 59 pada Peraturan Pemerintah Nomor 35 Tahun 2021 tentang Ketentuan Pesangon bagi Pekerja UMKM Perspektif Fiqh Siyasah - Safwan Alwi Harahap; Zaid Alfauza Marpaung (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This research discusses legal certainty in providing severance pay to MSME workers, in article 59 of government regulation Number 35 of 2021 states that the amount of severance pay given by MSME entrepreneurs is based on an agreement between the employer and employee, this makes the transaction appear to have no legal certainty. . This research uses a normative legal research method with a literature study approach that involves analysis of sources of Islamic law such as the Koran, Hadith and the opinions of leading scholars. The results of this research found provisions in Article 59 in government regulation Number 35 of 2021 which states that the amount of severance pay given by MSME entrepreneurs is based on an agreement between the employer and employee. However, it does not explain in detail the severance pay recommendations. This creates legal uncertainty and opens up opportunities for severance pay to be determined unilaterally by the employer. This also contradicts one of the principles of siyasa fiqh, namely the principle of justice.